The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.3390/ijerph16122187
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Attapulgite/CoFe2O4 Magnetic Composites for Efficient Adsorption of Tannic Acid from Aqueous Solution

Abstract: The use of attapulgite (ATP)-based materials for adsorption of pollutants from water and wastewater has received growing attention. However, recovering ATP-based adsorbents remains a challenge. In this study, a magnetic adsorbent ATP/CoFe2O4 with high tannic acid (TA) adsorptive capacity was fabricated via a facile co-precipitation approach and was well characterized. The loaded CoFe2O4 particles were embedded into the adsorbent surfaces to allow magnetic separability. For this material, its TA adsorption kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…To better demonstrate the excellent adsorption properties of HP-MIL-101, a more comprehensive comparison of the rate constant and adsorption capacity for the removal of TA with other materials reported in the literature is given in Table 3. 32,[37][38][39][40][41][42][43][44] It can be clearly seen that HP-MIL-101-30 displays a much higher adsorption rate than most reported materials at the same or even lower adsorbent dosage/TA concentration.…”
Section: Ta Adsorption Performancementioning
confidence: 85%
“…To better demonstrate the excellent adsorption properties of HP-MIL-101, a more comprehensive comparison of the rate constant and adsorption capacity for the removal of TA with other materials reported in the literature is given in Table 3. 32,[37][38][39][40][41][42][43][44] It can be clearly seen that HP-MIL-101-30 displays a much higher adsorption rate than most reported materials at the same or even lower adsorbent dosage/TA concentration.…”
Section: Ta Adsorption Performancementioning
confidence: 85%
“…The results revealed that the PO4 3-in the HAP@CoFe2O4 is involved in the reaction. After the adsorption reaction, a new peak appeared at 546.327 cm −1 , which corresponded to Co/Fe-O bonding [53,54]. A new absorption peak of the HAP@CoFe2O4 after the reaction appeared at 911 cm −1 , which was characteristic of UO2 2+ , providing strong evidence of uranium loading.…”
Section: U(vi) Removal Mechanismsmentioning
confidence: 94%
“…The influence of the contact time on the adsorption capacity of Aliz dye by both of clay and modified clay were conducted through batch experiments to achieve the equilibrium time, this PREPARATION AND CHARACTERIZATION OF GRAPHENE OXIDE -ATTAPULGITE ... procedure achieved by adding 0.01g of adsorbents (Ata or Ata-GO) into 10 ml dye solution, with initial concentration (40 mg/L) under shaking at temperature rang (20,25,30,35 ) o C with a thermostatic shaker (LabTech LSB-series Shaking Water Bath). After different time intervals, the solutions were centrifuged ( Hettich EBA 200) and volumes of 3ml supernatant were taken for spectrophotometrically measurements of Aliz dye content at its λ max .…”
Section: C-adsorption Experiments Proceduresmentioning
confidence: 99%
“…The EDX spectra of the studied surfaces were recorded by figures (8 ) and ( 9), From figure ( 8 ) show the several peaks of elements (Ru, Al, C, Si, O, Se, Fe, Ba, Co) in the spectrum analysis of the elements of the attapulgite clay but after the activation and modification of the carphene oxide sheets This led to a reduction in the weight ratios of most elements and some of them to zero such as (Co, Se),While the increase in the ratio of oxygen (5.6-6.2) and carbon ( 6.5-12.8 ), which confirms the occurrence of the process of modification of the graphene oxide, as shown in Figure (9) shows that several peaks of Ru, Al, C, Si, O, Fe, Ba), within the spectrum of elemental analysis of the attapulgite clay after activation and modification . [20 ] Fig. 6.…”
Section: D-edx Analysesmentioning
confidence: 99%